Lol p I–specific IgE and IgG synthesis by peripheral blood mononuclear cells from atopic subjects in SCID mice - Gagnon, Rémi; Boutin, Yvan; Hébert, Jacques (Journal of allergy and clinical immunology, 1995)
Background: The development of an animal model representative of the in vivo situation of human atopic diseases is always of interest for a better understanding of IgE production and regulation. Along these lines, mice with severe combined immunodeficiency (SCID mice) engrafted with lymphocytes from atopic subjects might be a suitable model for such studies. Objective: This study aims to analyze the production of Lol p I–specific IgE and IgG antibodies in SCID mice after transplantation of human peripheral blood mononuclear cells from atopic patients sensitive to grass pollens and from nonatopic donors. Methods: Peripheral blood mononuclear cells were transplanted into SCID mice, which were then challenged with Lol p I, and antibody responses (IgG and IgE) were analyzed over a 6-week period. Results: Total IgG antibody was measured in each mouse serum after transplantation. Also, most mice (regardless of whether donors were atopic) that were challenged with Lol p I produced specific IgG antibody. Total IgE antibody production was observed only in mice grafted with cells from atopic patients. Lol p I–specific IgE antibodies were also produced after immunization with Lol p I. Although IgG antibody response tended to plateau, the IgE antibody response increased until it peaked and declined thereafter. Interferon-γ was detected in sera from mice producing IgE antibody, which supports a possible role of interferon-γ in the decrease of IgE response. (J A LLERGY C LIN I MMUNOL 1995;95:1268-75.) Conclusion: This study suggests that the SCID mouse model could represent an interesting approach to studying specific, total IgG and IgE antibody production, and ultimately their regulation. (J A LLERGY C LIN I MMUNOL 1995;95:1268-75.)